Ag3PO4/g-C3N4 nanocomposites for photocatalytic degradating gas phase formaldehyde at continuous flow under 420 nm LED irradiation. (April 2020) - Rao, Xi; Dou, Hailong; Long, Dan; Zhang, Yongping
Abstract: A series of Ag3 PO4 /g-C3 N4 nanocomposites were synthesized by introducing various small amount of Ag3 PO4 in g-C3 N4 and subsequently employed for decomposing formaldehyde (HCHO) in continuous flow as photocatalysts. The results show that all the Ag3 PO4 /g-C3 N4 nanocomposites could perform a very stable photoactivity for degrading continuously flowing gaseous formaldehyde for at least 600 h. Especially, the HCHO degradation rate reached 22.4% by using 1AP-CN, which was 2.63 times as fast as that of g-C3 N4 . Our results reveal that the photoinduced electrons in conduction band (CB) are trapped by O2 to yield ⋅ O 2 −, while holes in valence band (VB) directly oxidize –OH and/or water to produce ·OH under visible light irradiation. As a consequence, HCHO is further oxidized to CO2 and H2 O by as-generate active species. Graphical abstract: XPS valence band spectrum of (a) CN, Ag3 PO4, 1AP-CN-before and 1AP-CN-after. The energy band schematic (b) of Ag3 PO4 /g-C3 N4 composites. Image 1 Highlights: Ag3 PO4 /g-C3 N4 nanocomposites were synthesized by introducing various small amount of Ag3 PO4 in g-C3 N4 . Ag3 PO4 /g-C3 N4 nanocomposites showed stable photoactivity for degrading continuously flowing gaseous formaldehyde. HCHO degradation rate reached 22.4% by using 1AP-CN, which was 2.63 times as fast as that of g-C3 N4